2002
DOI: 10.1152/ajpcell.00331.2001
|View full text |Cite
|
Sign up to set email alerts
|

Proadipogenic effect of leptin on rat preadipocytes in vitro: activation of MAPK and STAT3 signaling pathways

Abstract: Because leptin has recently been shown to induce proliferation and/or differentiation of different cell types through different pathways, the aim of the present study was to investigate, in vitro, the influence of leptin on adipogenesis in rat preadipocytes. A prerequisite to this study was to identify leptin receptors (Ob-Ra and Ob-Rb) in preadipocytes from femoral subcutaneous fat. We observed that expressions of Ob-Ra and Ob-Rb increase during adipogenesis. Furthermore, leptin induces an increase of p42/p44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
96
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 68 publications
9
96
1
6
Order By: Relevance
“…Consistent with this hypothesis, the present study demonstrates that leptin stimulates the secretion of macrophage LPL in vitro. In accordance with one previous study using preadipocytes (40), we found that leptin enhances LPL gene expression in macrophages. Although we did not perform run-on assays, our data showing that induction of LPL mRNA levels by leptin parallels the increase in LPL synthesis and secretion suggest that macrophage LPL regulation in response to leptin takes place at the transcriptional level.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with this hypothesis, the present study demonstrates that leptin stimulates the secretion of macrophage LPL in vitro. In accordance with one previous study using preadipocytes (40), we found that leptin enhances LPL gene expression in macrophages. Although we did not perform run-on assays, our data showing that induction of LPL mRNA levels by leptin parallels the increase in LPL synthesis and secretion suggest that macrophage LPL regulation in response to leptin takes place at the transcriptional level.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence that the conventional PKC selective inhibitor, GF109203X, abrogates the effect of leptin on macrophage LPL expression further stresses the key role of the conventional PKC isoenzymes in the regulation of macrophage LPL by leptin. Previous studies have demonstrated that PKC is involved in AP-1 activation (46) and that leptin stimulates c-fos expression (40). On the basis of these results, it is tempting to postulate that the activation of PKC by leptin that we documented in the present study could result in the binding of its downstream target, c-fos, to the AP-1 sequence of the LPL gene promoter, thereby leading to an increased transcription rate of this gene.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…To correlate the biological activities of leptin with the expression of leptin receptors, we analyzed HSCs isolated from four different donors using antibodies recognizing all ObR isoforms. An approximately 190-kd band representing ObRb, as reported in other cell types or in stable HSC lines, [16][17][18] was found in all isolates (Fig. 3A), together with faster migrating bands that are likely due to ObRa and/or other "short" isoforms.…”
Section: Leptin Upregulates Mcp-1 and Vegf Secretionsupporting
confidence: 73%
“…The Jak/Stat signaling pathway plays a critical role in mediating the effects of leptin, and Stat3 phosphorylation has been associated with ObRb activation in different cells, including HSCs. 17,18 To further establish the functionality of ObRb, we analyzed the effects of leptin on Stat3 activation (Fig. 3C).…”
Section: Leptin Upregulates Mcp-1 and Vegf Secretionmentioning
confidence: 99%